Performance Comparison of FLC, P&O, and IC Algorithms for MPPT Optimization in DB-Converter Under Dynamic Partial Shading - Hermansyah Hermansyah; Farid Dwi Murdianto; Alamsyah Achmad (Jurusan Pendidikan Teknik Elektro, 2025)
Solar energy can be converted into electrical energy using photovoltaic (PV) panels. The maximum output power of a PV system is achieved when solar irradiance falls directly on the panel's surface without obstruction. However, in practical conditions, solar irradiance is often disturbed by moving or static objects, which causes more than one maximum power point to appear on the P-V characteristic curve. This condition cannot be accurately addressed by conventional MPPT algorithms, thereby requiring advanced methods for partial shading conditions. Various partial shading algorithms have been developed, ranging from traditional methods to artificial intelligence-based approaches. This study presents a comparison between the FLC, P&O, and IC methods in the application of MPPT in the Double Boost Converter under dynamic partial shading conditions. The accuracy of the three methods is evaluated through simulation. The results indicate that all three methods are capable of addressing the effects of partial shading and can maintain high tracking accuracy. Moreover, the FLC method shows better performance in minimizing output oscillations, while the P and O method demonstrates superior tracking precision in reaching the global maximum power point.